Undetected locked-joint failures in kinematically redundant manipulators: a workspace analysis - Balakrishnan, Venkataramanan, author; Maciejewski, Anthony A., author; Goel, M., author; IEEE, publisher (Colorado State University. Libraries, 1998)
Robots are frequently used for operations in hostile environments. The very nature of these environments, however, increases the likelihood of robot failures. Common failure tolerance techniques rely on effective failure detection. Since a failure may not always be successfully detected, or even if detected, may not be detected soon enough, it becomes important to consider the behavior of manipulators with undetected failures. This work focuses on developing techniques to analyze a manipulator's workspace and identify regions in which tasks, characterized by sequences of point-to-point moves, can be completed even with such failures. Measures of fault tolerance are formulated to allow for the evaluation of the workspace.
Keywords: redundant manipulators; position control; fault tolerance; Jacobian matrices